Q: What is -x2 plus 6x plus 8?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-x2 + 6x + 16 = -(x2 - 6x - 16) = -(x - 8)(x + 2) = -(8 - x)(x + 2)

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

(-3,-1)

16 + 6x - x2 = 16 + 8x - 2x - x2 = 8*(2 + x) - x*(2 + x) = (8 - x)*(2 + x)

x2 + 6x = x*(x + 6)

Related questions

x2 + 6x + 8 = (x + 4)(x + 2)

-x2 + 6x + 16 = -(x2 - 6x - 16) = -(x - 8)(x + 2) = -(8 - x)(x + 2)

The quadratic expression x2+6x+8 when factorised equals (x+2)(x+4)

(-3,-1)

x2 + 6x + 8 =(x + 2)(x +4)

x2 + 6x = 16=> x2 + 6x - 16 = 0=> x2 + 8x -2x - 16 = 0=> (x+8)(x-2) = 0=> x = -8 or x = 2So, the solutions of the quadratic equation x2 + 6x = 16 are -8 and 2.

x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4

16 + 6x - x2 = 16 + 8x - 2x - x2 = 8*(2 + x) - x*(2 + x) = (8 - x)*(2 + x)

x2 + 6x = x*(x + 6)

-((x + 2)(x - 8))

x2 + 6x + 1 = 0 x2 + 6x + 9 = 8 (x + 3)2 = 8 x + 3 = ± 2√2 x + 3 = -3 ± 2√2 x ∈ {-3 - 2√2, -3 + 2√2}

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)